2011 6th International Workshop on Advanced Ground Penetrating Radar (IWAGPR) 2011
DOI: 10.1109/iwagpr.2011.5963881
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of current GPR ground wave methods for determining near-surface water contents

Abstract: We explore the stability of the Ground-Penetrating Radar (GPR) ground wave signal and its applicability for measuring near-surface water contents along a 0.6 km long measurement line, crossing several vegetated sand dunes at a semi-desert site in Northwestern China. We find that the direct ground wave signal is a stable proxy for measuring near-surface soil moisture. However, the absolute water content may be difficult to establish without additional auxiliary information (e.g. through TDR point measurements).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Provided highly accurate GPR observations are available over a preferably large range of soil water contents, monitoring soil water dynamics with GPR in connection with a suitable inversion scheme can in principle give access to soil hydraulic properties. So far, several studies have shown promise in inferring near-surface soil hydraulic properties based on time-lapse observations of soil water dynamics, using borehole GPR (e.g., Kowalsky et al, 2005;Rucker and Ferré, 2004;Looms et al, 2008), off-ground GPR (e.g., Jadoon et al, 2008;Lambot et al, 2009;Tran et al, 2014), and multi-offset on-ground GPR (Busch et al, 2013). Follow-ing a different approach, Moysey (2010) estimated soil hydraulic properties based on hydrologic trajectories derived from fixed-offset time-lapse monitoring of an infiltration experiment by on-ground GPR.…”
Section: Introductionmentioning
confidence: 99%
“…Provided highly accurate GPR observations are available over a preferably large range of soil water contents, monitoring soil water dynamics with GPR in connection with a suitable inversion scheme can in principle give access to soil hydraulic properties. So far, several studies have shown promise in inferring near-surface soil hydraulic properties based on time-lapse observations of soil water dynamics, using borehole GPR (e.g., Kowalsky et al, 2005;Rucker and Ferré, 2004;Looms et al, 2008), off-ground GPR (e.g., Jadoon et al, 2008;Lambot et al, 2009;Tran et al, 2014), and multi-offset on-ground GPR (Busch et al, 2013). Follow-ing a different approach, Moysey (2010) estimated soil hydraulic properties based on hydrologic trajectories derived from fixed-offset time-lapse monitoring of an infiltration experiment by on-ground GPR.…”
Section: Introductionmentioning
confidence: 99%